Java Sea Spirulina platensis chemical analysis and its protective ability against H2O2-exposed umbilical cord mesenchymal stem cells according to CD73, CD90, and CD105, viability, and HIF-1 alpha docking - Ani Retno Prijanti,, Retno Wahyu Nurhayati,, Febriana Catur Iswanti,, Zakiyatul Khoiriyah, Reni Paramita,,, Fadilah Fadilah, (Journal of Applied Pharmaceutical Science, 2022)
It is known that Spirulina has so many healing functions to overcome oxidative stresses correlated to the aging process. One of them is Spirulina platensis (SP), a microalga that is abundant in the Java Indonesian seas and has been widely cultivated. SP is able to improve mitochondrial function and is widely used as a food supplement according to its protein and content of omega-6, gamma linolenic acid, carotenoid, and various vitamins. This research was conducted to evaluate the effect of SP on cell viability and used a mesenchymal stem cell (MSC) culture as a model treated with hydrogen peroxide together with SP. SP was obtained from the Java Sea and extracted with ethanol. Its content was determined with the thin layer chromatography method, and the known content was docked with the HIF-1 protein. This extract was tested to overcome oxidative stress in umbilical cord-derived mesenchymal stem cells (UC-MSCs) treated with 100 and 300 μM hydrogen peroxide. Cell viability was assessed by a dye exclusion method with trypan blue. The specific surface markers (CD73, CD90, and CD105) were measured with flow cytometry to evaluate MSC stemness. The content of SP, phycocyanobilin and canthaxanthin, were considered candidates affecting HIF-1 protein regulation. The SP ethanol extract (125 ng/ml) maintained the viability and stemness of UC-MSCs during oxidative stress exposure with hydrogen peroxide. The phycocyanobilin and canthaxanthin of SP were considered candidate substances that could affect HIF-1 signaling, and the ability to overcome oxidative stress should be observed further.
Keywords: Spirulina platensis, MSC, CD70, CD90, CD105, HIF-1 alpha